Effects of work conditions and organisational strategies on nurses' mental health during the COVID‐19 pandemic. (14th October 2021) - Li, Tin‐May; Pien, Li‐Chung; Kao, Ching‐Chiu; Kubo, Tomohide; Cheng, Wan‐Ju
Abstract: Aims: This study aims to examine coronavirus disease 2019 (COVID‐19) pandemic‐related work factors for adverse effects on the mental health and whether organisational strategies attenuate these effects. Background: COVID‐19 pandemic has led to increased work burden and mental health risks for nurses. Methods: A total of 1499 Taiwanese full‐time nurses completed a web‐based questionnaire between July and December 2020. Pandemic‐related work conditions, namely, increased working hours, caring for COVID‐19 patients, occupational stigma and redeployment, were assessed. Organisational strategies to combat pandemic‐related work stressors including compensation to workers and adequate protection equipment were surveyed. Outcome measures were intention to leave, burnout and depression assessed using validated questionnaires. Results: Redeployment, increased working hours and occupational stigma were associated with adverse mental health and intention to leave in logistic regression analysis. Caring for COVID‐19 patients was negatively associated with depression. Adequate compensation for workers modified the association between redeployment and burnout. Conclusions: Pandemic‐related work conditions were associated with adverse mental health and intention to leave. Organisational strategies attenuated the adverse impact of the pandemic. Implications for Nursing Management: Efforts to decrease stigma and organisational strategies including compensation for workers and adequate protection equipment provision should be adopted to improve nurses' health during a pandemic.